DESAIN AWAL SPESIFIKASI PERANGKAT KERAS DAN JARINGAN HIGH PERFORMANCE COMPUTING UNTUK MENDUKUNG OPEN GOVERNMENT DI INDONESIA - R.A, Anton Siswo; Maulidia2, Nia (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
The need for transparency of data for a variety of public access, as well as guarantee the legal basis of the disclosure made significantly Open Government should be implemented in Indonesia. To support the Open Government thing to consider is the stability of access by the user, while the stability of access is influenced by two main issues, namely the specification of hardware (servers) and network.To optimize the server, we conducted a study of the technique In Memory Computing which is one technology that is rapidly growing in the era of Big Data Processing are included in clumps of High Performance Computing. Such technology is needed in areas that require very high computational intensity, because it has the ability to overcome the bottleneck that occurs in the system, especially on the permanent storage media such as Hard Disk Drive (HDD) and Solid State Disk (SSD). In this scientific study, carried out the design of hardware that can be applied to minimize the bottleneck that occurs and maximize the use of In Memory Computing technology, including the design of the specification as a central processing server to the network design specification required, so that can be easily done escalation when needed.